Environmental, social and personal factors influencing impulse buying behaviour among tourists patronizing premium outlets in Malaysia - Syed Ali, Sharifah Faridah (2020)
Shopping tourism in Malaysia is the major contributor to the national economy. As a matter of fact, in 2018, it contributed approximately RM28.20 million to the country economy. The establishment of premium outlets in Malaysia is one of the government initiatives to increase tourism revenue. However, this study found out that tourist did not feel satisfied with the store environment, price, discount, and the availability of variety offered by these premium outlets. Moreover, tourist expenditure on shopping in Malaysia has remained low, as compared to Seoul and London. Therefore, focusing on increasing the shopping expenditure among tourists, this study suggested impulse buying as one of the strategies to induce tourists to shop and subsequently, increase the tourism revenue. In particular, a conceptual framework that incorporated environmental, social, and personal factors, excitement, impulsiveness, and impulse buying behaviour at the premium outlets in Malaysia was proposed. The data collection was conducted at five premium outlets in Malaysia, namely Johor Premium Outlet (JPO), Mitsui Outlet Park (MOP), Freeport A’Famosa Outlet, Design Village Outlet (DVO), and Genting Premium Outlet (GPO). The sample population consisted of 440 local and international tourists who shopped and purchased at these outlets. Since there was no available list of local and international tourists at these outlets, purposive and quota sampling techniques were applied in this study. The international tourists were selected based on the Tourism Malaysia report on the top five countries with the biggest spenders in Malaysia. Then, the respondents were divided accordingly to the year of operation of these premium outlets. This study expanded the model of Floh and Madlberger (2013) through the incorporation of social and personal factors and replacement of shopping enjoyment with excitement to understand tourists’ impulse buying behaviour at the premium outlets in Malaysia. PLS-SEM was used to examine the relationship of these constructs (seven hypotheses). The results revealed environmental factors (i.e. sales promotion and variety of selection) as important elements that induce tourists to make a purchase impulsively. Interestingly, this study also confirmed the significant influence of self-concept on impulse buying behaviour. In other words, tourists are induced to make a purchase impulsively without being influenced by environmental or social factors. Additionally, this study demonstrated the full mediation effect of impulsiveness on the relationship between excitement and impulse buying behaviour. Moreover, this study provided valuable insights and understanding on the key factors that drive tourists to purchase impulsively. The retailers should provide a comfortable environment with attractive sales promotion and a variety of selection that would arouse tourists’ excitement and subsequently, lead them to purchase on impulse. Besides that, a variety of products or brands at these premium outlets would allow tourists to make a selection to express their identity and better-self. As for the policymakers, good quality of shopping place would help the industry to maintain the current shopping malls and minimise issues of low occupancy rate in the industry. This study was expected to assist policymakers in generating audit criteria to direct the best practices in these premium outlets in Malaysia. However, there are several limitations of this study that are worth mentioning. Firstly, the subject of the study was limited to premium outlet only. Additionally, this study carried out only the quantitative research method and no comparisons were made between international and local tourists in terms of their impulse buying behaviour. The data collection process was likewise conducted within a short period of time and involved a few nationalities.